CORRELATION BETWEEN KNOWLADGE OF SMOKING HAZARD AND SMOKING BEHAVIOR AMONG ADOLESCENTS at SMK PEMBANGUNAN NASIONAL PURWODADI - Mika Agustiana; Christina Nur Widayati; Fatchullah (LPPM Universitas An Nuur, 2026)
Background; smoking hes a negative impact on individual habits. The addictive nature of cigrattes makes smoking a habit that is difficult to eliminate. According to the Ministry of Healt (2024), the number of active smokers has reached 70 milion people,accounting for 7,4%. Based on data from BPS (2018), the smoking rate iun Indonesia reached 22,46%. According to Riskesdas (2018), central Java is the province with a smoking prevelance pf 23,19%. One of the causes of smoking behavior is a lack of knowledge about its dangers. The aim of this study was to determine the relationship between knowledge about the dangers of smoking and smoking behavior in adolescents at the Purwodadi National Development Vocational School. Method; this study was a quantitative researtch using a restroperctive approach and a case-control design. The sample consisted of 176 respondent out of a total population og 676 students. Data were collected using a questionnaire to measure knowledge and smoking behavior. Result; Respondents with low knowledge and smoking behavior totaled 58 (33,0%). A comparative test using the chi-square menthod with computer assistance showed a p-value of 0,000 < α (0,05), meaning Ho is rejected and Ha is accepted. Conclusion; There is a relationship between the level of knowledge about the dangers of smoking behavior. The Odds ratio was found to be 13.533, meaning respondents with poor knowledge are 13.533 times more likely to engage in smoking behavior.